PENGARUH MODEL HYRBRID LEARNING BERBASIS TECHNOLOGYCAL CONTENT KNOWLADGE ( TCK ) TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN GEOGRAFI KELAS X IPS DI SMA NEGERI 6 PADANG - Pratama, Wahyu; Rahmanelli, Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Based on the circular decree of the 4 Ministers Number 03/KB/2021 regarding guidelines for the implementation of learning during the Covid-19 period. With this policy, it is possible for schools to carry out hybrid learning, both by carrying out face-to-face learning activities by utilizing technology in each process. The purpose of this study was to determine the effect of using the Hybrid Learning Model on student learning outcomes. The method used in this study is a quantitative method with the type of experimental research with Pretest-Posttest control group design. The population of this research is class X IPS using purposive sampling technique, the research sample is class X IPS 1 and X IPS 3 SMA Negeri 6 Padang. Data collection techniques used are observation techniques for initial conditions, and test techniques to collect data on student learning outcomes. The data analysis technique used the Independent Samples T Test as a hypothesis test. The results of this study are based on proving the accepted hypothesis using the T test, where the calculation results obtained sig.(2-tailed) of 0.000 with a significant level of 0.005. From the results of the analysis, it is explained that there is a better influence in the use of content technology-based Hybrid Learning learning models in learning compared to conventional models, as well as the average student learning outcomes taught by the hybrid learning learning model is higher with a gain value of 0.76 taught.